The Impact of Preeclampsia Definitions on the Identification of Adverse Outcome Risk in Hypertensive Pregnancy: Analyses From the CHIPS Trial (Control of Hypertension in Pregnancy Study). Issue 2 (24th June 2022) - Magee, L.A.; Singer, J.; Lee, T.; Rey, E.; Asztalos, E.; Hutton, E.; Helewa, M.; Logan, A.G.; Ganzevoort, W.; Welch, R.; Thornton, J.G.; Woo Kinshella, M.L.; et al.
Abstract : ( BJOG . 2021;128:1373–1382) Hypertensive disorders of pregnancy include preeclampsia, gestational hypertension (developing at or after 20 wk' gestation), and chronic hypertension (diagnosed before 20 wk' gestation, or before pregnancy). Of these, preeclampsia is associated with the highest risks for parturient and neonate. Gestational or chronic hypertension often develops into preeclampsia. Preeclampsia is typically defined by new proteinuria, though patients with chronic or gestational hypotension may face severe complications without the presence of proteinuria. Some countries have adopted a broader definition of preeclampsia, not requiring proteinuria for diagnosis and also using evidence of placental or maternal end-organ dysfunction. This secondary analysis of the Control of Hypertension in Pregnancy Study (CHIPS) aimed to compare the abilities of the traditional and broad definitions of preeclampsia to identify patients with chronic or gestational hypertension at risk of adverse outcomes.